2013
DOI: 10.1002/ejsp.1986
|View full text |Cite
|
Sign up to set email alerts
|

Does remembering past ingroup harmdoing promote postwar cross‐group contact? Insights from a field‐experiment in Liberia

Abstract: In the aftermath of the Liberian civil wars, we investigated whether it is possible to systematically influence how people construe their group's role during the conflict and how this affects intergroup emotions and behavioral intentions. In a field experiment, 146 participants were randomly assigned to think about incidents of violence during the war that were either committed by fellow ingroup members (perpetrator‐focus) or against fellow ingroup members (victim‐focus). Adopting a perpetrator‐focus led to gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
51
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(57 citation statements)
references
References 57 publications
(91 reference statements)
4
51
0
Order By: Relevance
“…Results from these studies convergingly confirmed the differing needs structure in victims (or members of victimized groups) and perpetrators (or members of perpetrating groups) and how messages of acceptance and empowerment are facilitating reconciliation if they fit the needs of the recipient (group) (for an overview, see Shnabel & Nadler, 2015). Mazziotta et al (2014) have linked the different socio-emotional needs to potential differences in focus between perpetrators and victims. They proposed that victims' need for empowerment might direct their focus of attention towards the suffering of the ingroup and its primary goals.…”
Section: Theoretical Framework: the Needs-based Model Of Reconciliationmentioning
confidence: 76%
See 4 more Smart Citations
“…Results from these studies convergingly confirmed the differing needs structure in victims (or members of victimized groups) and perpetrators (or members of perpetrating groups) and how messages of acceptance and empowerment are facilitating reconciliation if they fit the needs of the recipient (group) (for an overview, see Shnabel & Nadler, 2015). Mazziotta et al (2014) have linked the different socio-emotional needs to potential differences in focus between perpetrators and victims. They proposed that victims' need for empowerment might direct their focus of attention towards the suffering of the ingroup and its primary goals.…”
Section: Theoretical Framework: the Needs-based Model Of Reconciliationmentioning
confidence: 76%
“…Based on the NBMR (Shnabel & Nadler, 2008) the present research tested the hypothesis that, following a transgression, victims and perpetrators differ in their focus of attention such that victims show a stronger self-focus than perpetrators (see also Mazziotta et al, 2014). To our knowledge, this assumption has received only indirect empirical support in previous research (e.g., in research on social rejection, e.g., Twenge et al, 2003;or entitlement, e.g., Chaitin & Steinberg, 2008).…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations